2011
DOI: 10.1007/s11214-010-9705-4
|View full text |Cite
|
Sign up to set email alerts
|

Microflares and the Statistics of X-ray Flares

Abstract: This review surveys the statistics of solar X-ray flares, emphasising the new views that RHESSI has given us of the weaker events (the microflares). The new data reveal that these microflares strongly resemble more energetic events in most respects; they occur solely within active regions and exhibit high-temperature/nonthermal emissions in approximately the same proportion as major events. We discuss the distributions of flare parameters (e.g., peak flux) and how these parameters correlate, for instance via t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
117
1
7

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
4
1

Relationship

4
5

Authors

Journals

citations
Cited by 150 publications
(137 citation statements)
references
References 148 publications
(205 reference statements)
12
117
1
7
Order By: Relevance
“…Its distribution in energy roughly follows a power law [85], which is consistent with observations over a large range of energies and with the concept of self-organized criticality; see e.g. the review [86]. In the coronal part of the volume, the typical energy released in a threedimensional model is of the order of 10 17 J (or 10 24 erg) [85], which is in the same range as the nanoflares originally predicted by Parker [87].…”
Section: (E) Nanoflares Nanoflare Storms and Braiding Of Fieldlinessupporting
confidence: 87%
“…Its distribution in energy roughly follows a power law [85], which is consistent with observations over a large range of energies and with the concept of self-organized criticality; see e.g. the review [86]. In the coronal part of the volume, the typical energy released in a threedimensional model is of the order of 10 17 J (or 10 24 erg) [85], which is in the same range as the nanoflares originally predicted by Parker [87].…”
Section: (E) Nanoflares Nanoflare Storms and Braiding Of Fieldlinessupporting
confidence: 87%
“…These temperatures are significantly higher than those obtained for the hot component in our analysis. Part of this discrepancy might be explained by the different sensitivity of the instruments, due to the different spectral band, that would lead the instruments to be sensitive to different parts a broad emission measure distribution (Peres et al 2000;Hannah et al 2011). The average emission measure obtained from thermal fitting of RHESSI microflares is about 2−3 × 10 46 cm −3 , which is much larger than the emission measure of the hot components that we obtain.…”
Section: Discussioncontrasting
confidence: 63%
“…2 and 5, although in a harder energy band (Hannah et al 2008(Hannah et al , 2011. The different energy bands correspond to different fitting parameters, as expected from experimental bias (Hannah et al 2011). We can equally attempt a comparison if we consider microflares either included in or excluded from our data.…”
Section: Discussionmentioning
confidence: 90%
“…Yet in one important aspect they differ significantly; their spectra above 10 keV (usually interpreted as non-thermal emission) are generally steep compared to large flares; interpreted as a power-law the spectral index of microflares is generally between −5 and −8 (see Benz & Grigis 2002;Krucker et al 2002;Christe et al 2008;Hannah et al 2008a), while for large flares it typically ranges from −2.5 to −4, (Saint-Hilaire et al 2008), although there are some notable exceptions (Hannah et al 2008b;O'Flannagain et al 2013). A recent full review of microflare properties may be found in Hannah et al (2011). One possible interpretation of this finding is that microflares are not as efficient particle accelerators as large flares.…”
Section: Introductionmentioning
confidence: 99%